2022
DOI: 10.2460/javma.20.10.0564
|View full text |Cite
|
Sign up to set email alerts
|

Use of a canine melanoma vaccine in the management of malignant melanoma in an African penguin (Spheniscus demersus)

Abstract: CASE DESCRIPTION A 25-year-old 4.4-kg male aquarium-hatched African penguin (Spheniscus demersus) was evaluated because of a raised 1.5 × 0.5-cm pigmented mass extending from within the right naris noted 2 days earlier. CLINICAL FINDINGS The penguin had a raised pigmented mass extending out from the right naris and onto the upper beak. Histologic examination of excisional biopsy specimens confirmed a diagnosis of malignant melanoma. A treatment plan including administration of meloxicam, radiation therapy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It appears to improve survival by inducing tumor-specific antibodies, cytotoxic T-cells, and antitumor responses. 46 Administration of the vaccine typically involves an initial administration of 4 intradermal injections, biweekly, followed by boosters every 6 months thereafter. 45,47 Currently, this vaccine has been reported to be used off-label in cats, penguins, a tiger, and a lion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears to improve survival by inducing tumor-specific antibodies, cytotoxic T-cells, and antitumor responses. 46 Administration of the vaccine typically involves an initial administration of 4 intradermal injections, biweekly, followed by boosters every 6 months thereafter. 45,47 Currently, this vaccine has been reported to be used off-label in cats, penguins, a tiger, and a lion.…”
Section: Discussionmentioning
confidence: 99%
“…45,47 Currently, this vaccine has been reported to be used off-label in cats, penguins, a tiger, and a lion. 21,46 One study specifically evaluating the use of the xenogeneic melanoma vaccine in cats included 24 cases of feline melanoma, with 8 cases involving the oral cavity. The study revealed an 11% adverse effect rate, although these adverse effects were considered to be minimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports for use of Oncept in zoo species also exist. Examples include use in a wild mountain Gorilla (Gorilla beringei beringei) [48] with melanoma arising from the left lip commissure and metastases to multiple lymph nodes, an African lion (Panthera leo) [49] with melanoma of the lip, and an African penguin (Spheniscus demersus) [50] with melanoma arising inside the nares.…”
Section: Use In Other Speciesmentioning
confidence: 99%